TEACHING SPEAKING IN BLENDED LEARNING COMMUNITY - Sri Utami Dewi (STKIP PGRI Trenggalek, 2018)
Speaking is the most difficult skill for most learners who learn it as a second or foreign language due to their low proficiency. The application of blended learning model is expected can be a solution for the learners who has problem with speaking skills. Meanwhile, learners’ motivation to study and get involved in learning is also become crucial aspects to achieve the learning objectives since the teacher’s role is only as a facilitator. Teaching speaking using blended learning model is divided into three major activities; these are warming up, main activities and closing. Some applications and internet connection are also needed to support the learning process. This learning model will give benefit both for the learners and also the teacher